FORMS OF THE DIFFERENTIATION OF WORK WITH TEXTS IN PRIMARY SCHOOLS - Shevchuk, Larysa (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
This article justifies the importance and relevance of the use of differentiated work with texts starting with primary school. Results of the analysis of scientific and methodological literature, modern teaching practice on the reflection of the issue of using various forms and kinds of differentiation are described. It is underlined that differentiation of learning is based on discovering and reckoning with the individual characteristics of students and their differences. Individualization of teaching is interpreted as the highest stage of differentiation. Described ways and kinds of differentiation are the most adequate for the effective differentiated work with texts. Such criteria as the level of a student’s autonomy in completing tasks and the complexity of an educational work are at the heart of this classification. Varying levels of autonomy in educational work are ensured by joint completion of tasks, independent work, playing the role of a consultant. The difficulty of tasks is provided by various ways of formulating tasks and the variation in their content. One more regulator of the tasks’ difficulty is the volume and the level of difficulty of texts. As a result of effectiveness checks of the use of aforementioned forms and ways of differentiation of primary school students with educational texts significant positive effect was found.